Open-Ended Problems as a Strategy in Mathematics Modules to Enhance Students’ Mathematics Computational Thinking - Abdul Aziz; Sugeng Sutiarso; Caswita Caswita (Mandalika Mathematics and Educations Journal, 2025)
Computational thinking (CT) is a key competency in 21st-century mathematics education. However, Indonesian students still face challenges in decomposition, abstraction, and algorithmic reasoning due to learning resources dominated by single-solution problems. This study developed and evaluated a mathematics module based on open-ended problems to enhance students’ CT skills in quadratic functions. The research adopted an R&D approach using the ADDIE model, including analysis, design, development, implementation, and evaluation. The process involved needs, curriculum, and learner analyses, followed by expert validation, practicality testing, and effectiveness evaluation. Three experts validated the module, while teachers and students assessed its practicality. Effectiveness was tested using a quasi-experimental pretest–posttest control group design involving 61 high school students. Data were analyzed using descriptive statistics, N-Gain, and inferential tests. Results showed the module was valid, practical, and effective in improving CT skills. The experimental group achieved significantly higher N-Gain (p < 0.05) than the control group, with abstraction and pattern recognition showing the greatest improvement.